Man of iron - Wajda, Andrzej, 1926-; Radziwilowicz, Jerzy; Janda, Krystyna; Walesa, Lech, 1943-; Walentynowicz, Anna.; Scibor-Rylski, Aleksander; Film Polski; MGM/UA Home Video (Firm) ([Poland] : Film Polski ; Santa, CA : Distributed by MGM/UA Home Video, 1981)
The Polish Solidarity strike takes place at the Gdansk shipyard in the summer of 1980. An alcoholic TV journalist is ordered to smear one of Solidarity's key figures, coined the "man of iron."
MGM/UA Home Video: M204544.
Polish with English subtitles.
"Grand prize winner 1981 Cannes Film Festival"--Container.
Screenplay by Aleksander Scribor-Rylski ; directed by Andrej Wajda.
Jerzy Radziwilowicz, Krystyna Janda, Marian Opania, Wieslawa Kosmalska, Irena Bynska, Boguslaw Linda ; with Lech Walesa, Anna Walentynowicz.
Rated PG.
Keywords: Protest movements -- Fiction; Shipyards -- Poland -- Fiction; Feature films; Poland -- Fiction